2018
DOI: 10.1371/journal.pone.0196281
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis disease activity score is related to NSAID use, especially in patients treated with TNF-α inhibitors

Abstract: BackgroundNon-steroidal anti-inflammatory drugs (NSAIDs) are regarded as the cornerstone of conventional treatment for AS. However little is known about concomitant NSAID use during treatment (with TNF-α inhibitors) in daily clinical practice.Methods and findingsConsecutive patients from the GLAS cohort were included. NSAID use and ASAS-NSAID index were evaluated at group level and at individual patient level during 52 weeks of follow-up. Analyses were stratified for treatment regimen. Generalized estimating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
9
2
1
Order By: Relevance
“…Nevertheless, in contrast to our ndings, the authors also reported that baseline NSAID use was similar in the TNFi and conventional treatment groups (79% vs 74%; p=0.131) (17). The reason for the high NSAID use in both treatment groups was not clear in this study because baseline disease activity was higher in the patients who were put on TNFi treatment (17).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in contrast to our ndings, the authors also reported that baseline NSAID use was similar in the TNFi and conventional treatment groups (79% vs 74%; p=0.131) (17). The reason for the high NSAID use in both treatment groups was not clear in this study because baseline disease activity was higher in the patients who were put on TNFi treatment (17).…”
Section: Discussioncontrasting
confidence: 99%
“…It was also shown in an observational study that treatment with tumor necrosis factor inhibitor (TNFi) was associated with a decrease in the proportion as well as the dosage of the NSAIDs in patients with axSpA in a real-life setting (16). Recently, another observational study revealed that longitudinal NSAID use was associated with disease activity, particularly in patients treated with TNFi (17).…”
Section: Introductionmentioning
confidence: 99%
“…After 12 months of follow-up, both groups had similar activity scores (BASDAI=3.4 and ASDAS=2.2 vs. BASDAI=3.7 and ASDAS=2.3, respectively). Among patients who received conventional treatment, 82% maintained a sustained response with NSAIDs after 52 weeks [55]. Despite being observational studies whose primary objective was not to evaluate the response to treatment, the high rate of drug retention observed over time suggested a sustained efficacy of NSAIDs.…”
Section: Namentioning
confidence: 99%
“…DIC with several anti‐inflammatory, antipyretic, and analgesic properties is widely being used for the treatment of inflammatory disease like rheumatoid arthritis, spondylitis ankylosing, and post‐operative and post‐chemoradiotherapy inflammations. Unfortunately, besides the therapeutic benefits of DIC administration, its chronic uses induced nephrotoxicity and renal failure .…”
Section: Discussionmentioning
confidence: 99%